1999
DOI: 10.1046/j.1526-4610.1999.3909654.x
|View full text |Cite
|
Sign up to set email alerts
|

Objective Behavior Associated With an “Ordinary” Mild Headache: A Surprising Failure of Pain Onset to Signal Self‐protective or Self‐regulatory Behavior

Abstract: The data suggest unusually ambitious, effortful task engagement may contribute to the onset of mild "ordinary" headache. This possibility requires further examination under other controlled conditions as well as in the natural environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…A modified version of the Subjective Ratings Scales (SRS; Thackray et al, 1977), a self-report measure of acute emotion, was used to assess stress symptoms experienced prior to, during and immediately following the experimental stress task. The SRS has been used in other studies of stress and headaches (Hovanitz et al, 1999). The SRS is comprised of six items assessing attention, energy, strain, interest, irritation and stress that are rated on 9-point scales ranging from 1 (corresponding with the most negative rating of a particular item, i.e.…”
Section: Psychological Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified version of the Subjective Ratings Scales (SRS; Thackray et al, 1977), a self-report measure of acute emotion, was used to assess stress symptoms experienced prior to, during and immediately following the experimental stress task. The SRS has been used in other studies of stress and headaches (Hovanitz et al, 1999). The SRS is comprised of six items assessing attention, energy, strain, interest, irritation and stress that are rated on 9-point scales ranging from 1 (corresponding with the most negative rating of a particular item, i.e.…”
Section: Psychological Measuresmentioning
confidence: 99%
“…Stress is the most common precipitant of TTH identified by patients (Rasmussen, 1993) and prolonged laboratory stressors may elicit headaches in susceptible individuals (Hovanitz et al, 1999(Hovanitz et al, , 2002. We thus reasoned that if depression increases vulnerability to TTHs, depressed individuals would be more vulnerable than similar euthymic individuals to TTHs induced by laboratory stress.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Hovanitz [19] found that students who report frequent headaches also perceived themselves as putting forth more effort when compared to the average student at their university. The headache-prone individuals report of relatively higher effort expenditure on academic-related tasks was confirmed by task analysis in two laboratory-based studies [20,21].…”
Section: Introductionmentioning
confidence: 71%
“…In that experimental study, 29 subjects who developed a headache were found to choose significantly more difficult problems than subjects who remained headache free. These results were not anticipated—indeed, the hypothesis of that study was “to determine whether the onset of head pain was associated with a reduction in effort expenditure.” Because heightened ambition during a headache state, observed behaviorally in that study, does not seem consistent with a self‐perception that ability to work has declined, the possibility is raised that those experiencing headache may not be aware of their performance efforts.…”
mentioning
confidence: 96%
“…The hypothesis addressed in Hovanitz et al 29 was most meaningfully evaluated by distinguishing between the immediate cause of headache (recall of a recent stressor) and ambition (choice of math problem difficulty). As excessive effort, objectively assessed, was found before as well as after headache onset, the results were interpreted as suggesting that excessive ambition may be etiologically related to headache onset.…”
mentioning
confidence: 99%